Smart Nanovesicles for Drug Targeting and Delivery - Marianecci, Carlotta; Carafa, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Nanovesicles are highly-promising systems for the delivery and/or targeting of drugs, biomolecules and contrast agents. Despite the fact that initial studies in this area were performed on phospholipid vesicles, there is an ever-increasing interest in the use of other molecules to obtain smart vesicular carriers focusing on strategies for targeted delivery. These systems can be obtained using newly synthesized smart molecules, or by intelligent design of opportune carriers to achieve specific delivery to the site of action.
English
Keywords: n/a; protein corona; buspirone; drug delivery; Plectranthus ecklonii; antiproliferative activity; pancreatic ductal adenocarcinoma; tetraethyl orthosilicate; cancer therapy; nanoparticles; cationic liposomes; Ibuprofen; SBA-15; gastrointestinal stability; mesoporous silica nanoparticles; Parvifloron D; anti-tumor drugs; liposomes; gingiva mesenchymal stromal cells; soy lecithin liposomes; MCM-41; lipophilic compound; multifunctional liposomes; caryophyllene sesquiterpene; drug loading; lamellarity; hCMEC/D3 cells; gold shell; magnetic/plasmonic nanoparticles; pH-sensitive niosomes; hot flushes; nasal delivery system; andrographolide; brain delivery; pancreatic cancer; Pain; exosomes; NSAIDs; freeze-drying; manganese ferrite; surfactant; cytotoxicity; paclitaxel; ovariectomized rat; PAMPA; uptake and safety; nanovesicular nasal carrier; Stober$1 (Bs synthesiss; Analgesia; protocells; nanocochleates; squamous cell carcinoma